2022
DOI: 10.1007/s12186-022-09297-5
|View full text |Cite
|
Sign up to set email alerts
|

Ready? Steady? Grow! Readiness for Participating in Learning in Dual Education

Abstract: published version features the final layout of the paper including the volume, issue and page numbers. Link to publication General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.• Users may download and print one copy of any publication from the public portal for the purpose of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…We did find though that new nurses from Cluster #3 (highly academically prepared and highly self-competent) transfer to a higher degree than nurses from the other clusters. From a theoretical point of view, this lines up with De Groof et al [31] when stating that students with previous work experience in health are more mature when facing the job for which they have been preparing themselves. However, many of the students with previous work experience completed previous study too; so, the question is whether this relation is based on the previous work experience in health of the new nurses or whether it is caused by their previous study in the field [38].…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…We did find though that new nurses from Cluster #3 (highly academically prepared and highly self-competent) transfer to a higher degree than nurses from the other clusters. From a theoretical point of view, this lines up with De Groof et al [31] when stating that students with previous work experience in health are more mature when facing the job for which they have been preparing themselves. However, many of the students with previous work experience completed previous study too; so, the question is whether this relation is based on the previous work experience in health of the new nurses or whether it is caused by their previous study in the field [38].…”
Section: Discussionmentioning
confidence: 76%
“…Pool and Swell [30] considered that working is a valuable experience, but it must be related to the studies students are enrolled in to be meaningful. This is why De Groof et al [31] recently confirmed that workplace learning allows students to acquire competences directly related to their job while working. Along the same lines, Nebot [32] found, in his study on the perceptions and experiences of nursing students before the clinical practice performed during the degree, that there are differences between students with previous work experience and those who do not have it; for example, students with previous experience are not as afraid of using their technical skills compared to students who have no work experience.…”
Section: Learning Transfer Factors In Nursing Professionalsmentioning
confidence: 99%
“… 63 a Dual learning = includes learning in working environments and learning in school environments. Dual learning assumes that pupils and students not only apply what they have learned at school in the workplace, but also gain knowledge, skills and attitudes in the workplace which were not introduced in the school environment [ 34 ]. …”
Section: Resultsmentioning
confidence: 99%
“…Finally, our findings are distinctive as it investigates the relationships among a growth mindset, meaningfulness at work, in-role performance and job crafting with corporate trainers. The roles of corporate trainers have been evolved to be more versatile and adaptable to match their capabilities with changing trends, technologies and workplace needs (De Groof et al, 2022;George, 2023). Corporate trainers should be proactive and possess the necessary skills to influence trainees for satisfactory performance and future growth (Ahmed and Khaleque, 2017), which is well aligned with a growth mindset and job crafting.…”
Section: Discussion and Theoretical Implicationsmentioning
confidence: 99%
“…To explore the impact of mindsets on workplace learning and performance (De Groof et al, 2022), this study draws on the JCM (JCM; Hackman and Oldham, 1976) and JCT (JCT; Wrzesniewski and Dutton, 2001). The JCM underscores specific job attributes, such as skill variety, task identity, task significance, autonomy and feedback, positing that these characteristics enhance motivation, satisfaction and performance (Hackman and Oldham, 1976).…”
Section: Theoretical Background and Hypothesis Developmentmentioning
confidence: 99%